Appearance and recurrence of odontogenic keratocysts - Pylkkö Jaakko; Willberg Jaana; Suominen Auli; Laine Hanna K; Rautava Jaana (WILEY, 2025)
Objective: The purpose of this study was to evaluate the appearance, histopathological features, and recurrence of odontogenic keratocysts (OKCs) from a large single institute registry over a 36-year period.
Materials and methods: A total of 226 cases of OKC were identified in 174 patients over a 36-year period in a single institute in Southwestern Finland. Histological specimens were re-evaluated. The patient's age, sex, location, recurrence, and histopathological features of the OKC were the study variables.
Results: OKCs occurred more frequently in men, the mean age was 46 years, and the most frequent site was the lower jaw. Recurrence rate was 21%. Histopathologically, inflammation was present in 95% and satellite cysts in 10% of cases. In patients diagnosed with satellite cysts, OKC recurred in 50% of cases, while the corresponding figure for patients without satellite cysts was 17%.
Conclusions: Compared with the literature, patients were older and inflamed cysts were found more frequently. Satellite cysts occurred only in association with chronic inflammation. Based on the results, regular radiographic evaluation is important among patients aged 10-29 years to detect OKCs and to treat them before enlargement, infection, and inflammation. Satellite cysts should be reported and may be a sign of increased risk of OKC recurrence.